AN ANALYSIS OF CONVERSATION STRUCTURE IN LITTLE BIG SHOT AMERICA - Aji Rizki Amalia (LEAD (Language, Education and Development), 2022)
Conversation analysis is used to analyze conversation among people. It can be done from the point of view of conversational structure and also part of conversation. This mini research focuses on the conversational structure and strategy used in conversation. Two main focuses on the research are global structure and Local structure. Global structure is overall organization of conversation, which is opening, body and closing. Local structure consists of the use of turn-taking strategy, the existence of adjacency pairs and how the speakers give feedback. The object of the study is talent talk show Little Big Shot America, in season 1, episode 1. There were many researches about conversation analysis with TV show as the object study. But this study is different because the show involves kids as the guest. It leads to the result that many strategies used in conversation different from the strategy which involves both adults as the speaker and audience. Although there are many strategies used in the show, the host mostly used Turn-claiming strategy to keep the floor and to let the kids “return” to the turn that they are engaged. It happened because kids often move from one turn to another, jumping from one topic to another one.